Hydrothermally grown ZnO nanowire array as an oxygen vacancies reservoir for improved resistive switching. (30th June 2020) - Fra, V; Beccaria, M; Milano, G; Guastella, S; Bianco, S; Porro, S; Laurenti, M; Stassi, S; Ricciardi, C
Abstract: Resistive switching (RS) devices based on self-assembled nanowires (NWs) and nanorods (NRs) represent a fascinating alternative to conventional devices with thin film structure. The high surface-to-volume ratio may indeed provide the possibility of modulating their functionalities through surface effects. However, devices based on NWs usually suffer from low resistive switching performances in terms of operating voltages, endurance and retention capabilities. In this work, we report on the resistive switching behaviour of ZnO NW arrays, grown by hydrothermal synthesis, that exhibit stable, bipolar resistive switching characterized by SET/RESET voltages lower than 3 V, endurance higher than 1100 cycles and resistance state retention of more than 10 5 s. The physical mechanism underlying these RS performances can be ascribed to nanoionic processes involving the formation/rupture of conductive paths assisted by oxygen-related species in the ZnO active layer. The reported results represent, to the best of our knowledge, the best resistive switching performances observed in ZnO NW arrays in terms of endurance and retention.